2003
DOI: 10.1097/01.asn.0000092145.90389.65
|View full text |Cite
|
Sign up to set email alerts
|

Salt Intake, Oxidative Stress, and Renal Expression of NADPH Oxidase and Superoxide Dismutase

Abstract: Abstract. The hypothesis that a high salt (HS) intake increases oxidative stress was investigated and was related to renal cortical expression of NAD(P)H oxidase and superoxide dismutase (SOD). 8-Isoprostane PGF 2␣ and malonyldialdehyde were measured in groups (n ϭ 6 to 8) of conscious rats during low-salt, normal-salt, or HS diets. NADPH-and NADH-stimulated superoxide anion (O 2 ·Ϫ ) generation was assessed by chemiluminescence, and expression of NAD(P)H oxidase and SOD were assessed with real-time PCR. Excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
239
5
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(265 citation statements)
references
References 47 publications
19
239
5
2
Order By: Relevance
“…The decrease in the SOD isoforms indicates a reduced ability to eliminate ·O 2 ˉ in the presence of canola oil and salt. High salt intake (6%) has been shown to reduce renal expression of CuZn-SOD and Mn-SOD in Sprague-Dawley rats [23]. The present study has also showed that p22 phox and NOX2 mRNA expression was reduced in the canola oil group with the presence of salt, indicating that ·O 2 ˉ generated from NADPH oxidase may be decreased.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The decrease in the SOD isoforms indicates a reduced ability to eliminate ·O 2 ˉ in the presence of canola oil and salt. High salt intake (6%) has been shown to reduce renal expression of CuZn-SOD and Mn-SOD in Sprague-Dawley rats [23]. The present study has also showed that p22 phox and NOX2 mRNA expression was reduced in the canola oil group with the presence of salt, indicating that ·O 2 ˉ generated from NADPH oxidase may be decreased.…”
Section: Discussionsupporting
confidence: 65%
“…The increased plasma and RBC MDA concentration indicates an increased amount of ROS induced lipid peroxidation, which may be due to the salt loading in combination with the diets. A previous study found an increase in urine MDA concentration in Sprague-Dawley rats as a result of salt intake [23]. They found a difference between the low salt (0.03%) and normal salt (0.3) groups, and between the low salt and high salt (6%) groups.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations